2019
DOI: 10.1111/tbj.13294
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of young women with breast cancer: Public vs private hospitals

Abstract: Disparities in breast cancer treatment have been documented in young and underserved women. This study aimed to determine whether surgical disparities exist among young breast cancer patients by comparing cancer treatment at a public safety‐net hospital (BH) and private cancer center (PCC) within a single institution. This was a retrospective study of young women (<45) diagnosed with invasive breast cancer (stage I‐III) from 2011‐2016. Patient information was abstracted from the breast cancer database at BH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…13,14 This racial disparity in mortality has been partially attributed to racial differences in stage of presentation, 15,16 molecular subtype, [17][18][19] and disparities in treatment. 13,[20][21][22][23] Nevertheless, this mortality disparity persists even in ductal carcinoma in situ, 14 the earliest and curable stage of disease. Black women are more likely to have poor tumor prognostic features such as high-grade, more aggressive breast cancer molecular subtypes (eg, triple-negative breast cancer), and lymph node metastasis at diagnosis.…”
Section: Breast Cancer In Black Womenmentioning
confidence: 99%
“…13,14 This racial disparity in mortality has been partially attributed to racial differences in stage of presentation, 15,16 molecular subtype, [17][18][19] and disparities in treatment. 13,[20][21][22][23] Nevertheless, this mortality disparity persists even in ductal carcinoma in situ, 14 the earliest and curable stage of disease. Black women are more likely to have poor tumor prognostic features such as high-grade, more aggressive breast cancer molecular subtypes (eg, triple-negative breast cancer), and lymph node metastasis at diagnosis.…”
Section: Breast Cancer In Black Womenmentioning
confidence: 99%
“…Acknowledging the disparities in healthcare is important, in order to overcome the limitations. Five studies evaluated the disparities in AYA patients who underwent surgery for breast cancer [ 69 , 70 , 71 , 73 , 75 ]. As previously discussed, the timing to surgery influenced the oncologic outcomes in one study.…”
Section: Resultsmentioning
confidence: 99%
“…That same study found that Hispanic and African American patients (compared to non-Hispanic white), patients with public or no insurance (compared to private insurance), and patients with a low socioeconomic status (compared to a high socioeconomic status) were more likely to have a treatment delay of greater than 6 weeks, which was associated with worse outcomes [ 75 ]. In other studies, surgical management was found to be equivalent in public and private hospitals [ 69 ]; however, race was associated with undergoing a CPM, with white women being twice as likely to undergo a CPM than women of other racial groups [ 73 ]. The oncologic outcomes were found to vary with marital status, with a survival benefit of BCS over mastectomy observed in unmarried patients [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5] Existing disparities and the call for their elimination is more than 3 decades old, yet, prior studies have conflicting findings on whether a disparity exists. [6][7][8][9] The inequity in IBR had been reported to be associated with several factors such as income, insurance type, geographical region, ethnicity and race, still the most commonly found disparity in more than 70% of prior studies is the association with race. 6 Despite the growing body of evidence on disparity, there is a paucity of studies with robust statistical methods focusing on the main cause of this disparity.…”
Section: Introductionmentioning
confidence: 99%